Технология реабилитации стволов дымовых труб с утилизацией химически активных компонентов дымовых газов - Akel’ev Валерий; Zolotareva И.; Chervaneva Е. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2012)
In the article heat- mass- corrosion technology of metallic, ferroconcrete, brick chimneys rehabilitation analyzed. The elaborated rehabilitation technology differs from others by assembling of rehabilitation (glass-fibro-plastic) chimney realizes not as usually “from below to upwards”, but “from above to down”. The interior surface heat- mass- protection accompanied with chemically active components of smoke gases utilization by condensation can used for minimization of environment pollution